Structural Characterization and Tensile Properties of Untreated and Alkali Treated Water Hyacinth Fibre - Augustine Uchechukwu Elinwa; Awari Amma Ishaya (Green Engineering Society, 2026)
Water hyacinth (Eichhornia crassipes) is an abundant aquatic biomass whose utilisation as a reinforcement fibre is limited by high contents of hemicellulose, lignin, waxes, and inorganic deposits. This study evaluates the effect of 10 % NaOH treatment on the structural, chemical, thermal, and mechanical properties of water hyacinth fibres (WHF). Scanning electron microscopy with energy-dispersive spectroscopy (SEM/EDS), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), X-ray fluorescence (XRF), thermogravimetric analysis (TGA/DTG), and single-fibre tensile testing were employed. Alkali treatment induced extensive defibrillation of compact fibre bundles into individual microfibrils (≈2–7 µm), transformation of cellulose I to cellulose II, and a marked increase in crystallinity from approximately 25 % to 71 %. Potassium and chloride contents were reduced by more than 99 %, and the maximum thermal degradation temperature increased from about 337 °C to 367 °C. Tensile strength and Young’s modulus increased from 18.4 ± 3.1 MPa to 58.1 ± 2.9 MPa and from 1.42 ± 0.18 GPa to 4.83 ± 0.23 GPa, respectively. These results demonstrate that NaOH treatment effectively purifies and structurally optimises WHF, significantly enhancing its thermal resistance and mechanical performance for sustainable composite reinforcement applications.